Purple Cabbage Soaking Water as an Alternative Dye to Replace Eosin in Soil-Transmitted Helminth Egg Examination - Enjellika Fingka; Supriyanto; Slamet Slamet (Public Health Frontier, 2026)
Worm infestation remains a public health problem in Indonesia, caused by soil-transmitted helminth infections. The main worms causing human infection are Ascaris lumbricoides, Trichuris trichiura, Strongyloides stercoralis, and hookworm. The 2% eosin is a dye used to stain worm eggs to diagnose helminth infections through microscopic examination. Purple cabbage contains anthocyanin pigments that can impart red, purple, blue, green, and yellow colours. This study aims to explain the differences in staining results from varying soaking times for purple cabbage as an alternative dye to eosin in the examination of soil- transmitted helminth eggs. The research method used was quasi-experimental. The sampling technique used was purposive sampling. The examination method used was the native method (direct examination). The sample size in this study was 27. The treatment in this study was replicated nine times at each time variation: 24, 36, and 48 hours. The results indicated that the worm egg preparations using purple cabbage soaking water for 24 and 36 hours produced a blurred visual field, the worm eggs did not absorb the dye, and the egg parts were not visible. The worm egg preparations using purple cabbage soaking water for 48 hours produced a bright visual field, the worm eggs absorbed the dye, and the egg parts were visible. Based on the Cochran Q statistical test, the results obtained for purple cabbage soaked in water for 24, 36, and 48 hours showed an Asymp.Sig value